PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea mays saccharataSturt) DENGAN PEMBERIAN MIKORIZA DAN ROCK PHOSPHATE (BATUAN FOSFAT ALAM) DI LAHAN GAMBUT - Fajar Rizki Saputra; Murniati Murniati; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study is aimed at knowing the influence of mikoriza and rock phosphateand get a combination of good treatment for growth and production of sweet corn (Zea mays saccarata Sturt) on peat land. This research has been implemented from August 2016 to November 2016 at the research garden of Agriculture faculty University of Riau, at a village of Rimbo Panjang, Tambang, Kampar district. Research was conducted by experimental design factorial of 3 x 4, arranged completely random draft (CRD). Factor I is application of mikoriza, M0 = without mikoriza, M1 = mikoriza 10 g per plant, M2 = mikoriza 20 g per plant and factor II is application of rock phosphate, P0 = without rock phosphate, P1 = rock phosphate267,85 kg.ha-1, P2 = rock phosphate535,71 kg.ha-1 and P3 = rock phosphate803,57 kg.ha-1. The results showed that application of mikoriza 20 g per plant and rock phosphate535,71 kg.ha-1 increased the percentage of the mikoriza infection from 15,50% to 83,00%, high of plant from 185,88 cm to 227,48 cm, leaf wide from 341,97 cm2 to 545,06 cm2, stem diameter from 1,75 cm to 2,25 cm, speed up the time appears to be a male flower from 51,50 HST to 48,00 HST, diameterof cob from 4,63 cm to 5,31 cm and increasing production per plot from 2,30 kg 4,5 m-2 to 4,95 kg 4,5 m-2 compared application of mikoriza 0 g per plant and rock phosphate 535,71 kg.ha-1.Keywords : sweet corn, mikoriza, rock phosphate